Improving the Efficiency of Crystallization in the Sugar Industry: Alternative Technologies and Impurity Control - Tuzhilkin VI; Balykhin MG; Lukin ND; Kovalyonok VA; Gorbatov VM (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
The sugar industry has traditionally relied on the periodic boiling of sugar massecuites for crystallization, but this method is limited by its instability and lack of efficient control. Researchers have sought to modernize this process through continuous crystallization, yet high costs and design defects have hindered the widespread adoption of this technology. In response, the authors propose a semi-continuous crystallization technology that achieves results comparable to continuous crystallization without significant changes in equipment. Three new technologies for crystallization of traditional periodic boiling are also presented, using mathematical modeling to analyze and compare results. The authors emphasize the importance of improving the efficiency of the crystallization process for reducing fuel consumption and increasing yield of finished product. The article also addresses the impact of impurities on crystallization and presents a criterion function for considering the qualitative composition of impurity in sugar processing. This study provides a comprehensive evaluation of the potentials for innovative crystallization technologies in the sugar industry and the importance of impurity control.